Alterations in gut microbiota and metabolomic profiles in acute stroke: insights into brain–gut axis dysregulation - Chen, Jiajing; Wu, Xiaodan; Wang, Xintong; Yuan, Ruijia; Zhu, Qi (Frontiers in Microbiology, 2025)
IntroductionAcute stroke (AS) is a major public health issue globally, exhibiting high morbidity, disability rate, and mortality. Emerging research has demonstrated the critical roles of gut microbiota and its metabolites in pathogenesis, recovery, and prognosis of AS.MethodsIn this study, we investigated alterations in gut microbiota composition and metabolomic profiles in AS patients using 16S rRNA sequencing and untargeted liquid chromatography-mass spectrometry (LC-MS) metabolomics technology.ResultsThe results revealed significant changes in gut microbiota diversity and community structure in AS patients compared with healthy controls. Notably, the abundance of anti-inflammatory microbiota was increased significantly, accompanied by elevated levels of certain metabolites, such as 6,9,12,15,18,21-tetracosahexaenoic acid and bufadienolide, while levels of urobilin and andrenid acid were significantly reduced. Network analysis further uncovered the significant diferences in microbiota-metabolite interactions between AS patients and healthy controls, indicating gut ecosystem disruption and functional dysfunction in AS.DiscussionThis study sheds light on the mechanisms of brain-gut axis in AS, suggesting potential microbial and metabolite biomarkers, thus providing valuable insights into AS prediction and treatment.